Migrations. Theoretical development, empirical evidences and conceptual consistencies. The other frontiers in the migrant condition (Polis (Santiago), 2018)
The search for explicative and descriptive totally paradigms in Social Sciences is a constant which can not be ignored, in case of the social process which are migrations. However, the existence of theoretical and conceptual paradigms, for the reference and utility of instrumental knowledge and in the characterization and signification of the social and cultural meaning, -without disregarding the economical aspects-, of the process and its current spatial and temporal structural dimensions.The article pretends to exemplify certain migratory-processes general consistencies, which at the same time, imply limitations of the micro-macro investigation-theories, on social processes, in general, and the migration in particular. Consistencies referent to condition-consideration, construct, politics, and socio-cultural environment of the migrant. The role of local spaces as a reference, in which it is finally characterized, signified and considered, and the degree of flexibility in which the migrant-autochthonous  negotiations are resolved.
Keywords: migrant; paradigms; local spaces